Housing shock : the Irish housing crisis and how to solve it - Hearne, Rory (Policy Press, 2020)
Hearn contextualises the Irish housing crisis within its broader global context and examines its origins in terms of the extension of neoliberalism, marketisation and financialisation in housing. Using real voices and stories, he shows how the crisis is having profound impacts on equality, wellbeing and health.